2021
DOI: 10.2807/1560-7917.es.2021.26.13.2001782
|View full text |Cite
|
Sign up to set email alerts
|

Prior infection by seasonal coronaviruses, as assessed by serology, does not prevent SARS-CoV-2 infection and disease in children, France, April to June 2020

Abstract: Background Children have a low rate of COVID-19 and secondary severe multisystem inflammatory syndrome (MIS) but present a high prevalence of symptomatic seasonal coronavirus infections. Aim We tested if prior infections by seasonal coronaviruses (HCoV) NL63, HKU1, 229E or OC43 as assessed by serology, provide cross-protective immunity against SARS-CoV-2 infection. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Dugas et al and Greenbaum et al showed that high levels of anti-HCoV-OC43 or anti-HCoV-HKU1 S and N antibodies were associated with reduced severity of COVID-19 or hospital death in studies with a small number of samples ( Dugas et al, 2021 , Dugas et al, 2020 , Greenbaum et al, 2021 ). Unlike the above reports, Ringlander et al and Sermet-Gaudelus et al also showed that previously verified infections with seasonal HCoVs were not associated with protection against SARS-CoV-2 infection or disease exacerbation in adults or children, respectively ( Ringlander et al, 2021 , Sermet-Gaudelus et al, 2021 ). Indeed, our study showed there was no association between the antibody titers of seasonal HCoVs and disease severity in the early phase of COVID-19.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Dugas et al and Greenbaum et al showed that high levels of anti-HCoV-OC43 or anti-HCoV-HKU1 S and N antibodies were associated with reduced severity of COVID-19 or hospital death in studies with a small number of samples ( Dugas et al, 2021 , Dugas et al, 2020 , Greenbaum et al, 2021 ). Unlike the above reports, Ringlander et al and Sermet-Gaudelus et al also showed that previously verified infections with seasonal HCoVs were not associated with protection against SARS-CoV-2 infection or disease exacerbation in adults or children, respectively ( Ringlander et al, 2021 , Sermet-Gaudelus et al, 2021 ). Indeed, our study showed there was no association between the antibody titers of seasonal HCoVs and disease severity in the early phase of COVID-19.…”
Section: Discussionmentioning
confidence: 85%
“…Protein homology between SARS-CoV-2 and seasonal HCoV antigens is approximately 19.8% for S1, 39.9% for S2, and 33.0% for N ( Saletti et al, 2020 ). Potential cross-reactivity of immunity between SARS-CoV-2 and seasonal HCoVs has been reported, but it is unknown whether the humoral immunity induced by previous infections of seasonal HCoVs can prevent disease exacerbation ( Dugas et al, 2021 , Greenbaum et al, 2021 , Hicks et al, 2021 , Laing et al, 2020 , Mateus et al, 2020 , Ng et al, 2020 , Ringlander et al, 2021 , Sermet-Gaudelus et al, 2021 , Wang. et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…targeted to Spike or Nucleocapsid) that harbored moderate SARS-CoV-2 neutralising activity [24]. Whether this neutralising activity is due to previous HCoV infections is still unclear, with several studies finding little difference between SARS-CoV-2 seropositive and seronegative children in HCoV antibodies [15,25].…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…The magnitude of the antibody response to SARS-CoV-2 infection has been positively correlated with COVID-19 severity [18][19][20][21][22][23][24][25] , but the confounding effect of age on this association remains unresolved [26][27][28] . Even less understood is whether cross-reactive seasonal human coronavirus (HCoV) antibodies correlate with the kinetics of SARS-CoV-2 humoral responses across acute and post-acute timescales after SARS-CoV-2 infection [29][30][31][32] . Pre-existing HCoV antibodies that cross-react with but do not cross-neutralize SARS-CoV-2 have been detected 30,[33][34][35][36] , and recent infection with HCoVs has been correlated with reduced COVID-19 severity 37 .…”
Section: Introductionmentioning
confidence: 99%